2016
DOI: 10.1158/1078-0432.ccr-15-0487
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Breast Cancer Metastases Identifies Liver Metastasis–Selective Genes Associated with Adverse Outcome in Luminal A Primary Breast Cancer

Abstract: in collaboration with the TEX study group Abstract Purpose: The complete molecular basis of the organ-specificity of metastasis is elusive. This study aimed to provide an independent characterization of the transcriptional landscape of breast cancer metastases with the specific objective to identify liver metastasis-selective genes of prognostic importance following primary tumor diagnosis.Experimental Design: A cohort of 304 women with advanced breast cancer was studied. Associations between the site of recur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 42 publications
2
35
0
1
Order By: Relevance
“…Remarkably, a higher incidence of liver metastases was found in patients with breast cancer with HER2-positive status. This is consistent with previous studies that showed organ specificity associated with specific gene (14,25,30,31). An early study suggested that decreased or abnormal expression of a number of cell adhesion/junctional proteins, including claudin 4, 7, ZO-1, and g-catenin, correlated with breast cancer liver metastases (30).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Remarkably, a higher incidence of liver metastases was found in patients with breast cancer with HER2-positive status. This is consistent with previous studies that showed organ specificity associated with specific gene (14,25,30,31). An early study suggested that decreased or abnormal expression of a number of cell adhesion/junctional proteins, including claudin 4, 7, ZO-1, and g-catenin, correlated with breast cancer liver metastases (30).…”
Section: Discussionsupporting
confidence: 92%
“…As a result, the changes caused by distant relapse and treatment exposure could be potential confounding factors in the prognostic assessment (12). In addition, the prognosis of patients with liver metastases from breast cancer is usually extremely poor, with 5-year survival rates of only 3.8% to 12% (6,(13)(14)(15). Because liver metastases have a significant influence on the morbidity and prognosis of patients with breast cancer, the early detection of liver metastases is of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is well‐known that liver is the third most common site for the metastasis of BCa, resulting in the poorer prognosis than local/regional, bone, and lung metastases (Kimbung et al, 2016; Ma et al, 2015; C. Zhang et al, 2018). The standard of care for patients with BCa liver metastasis is palliative therapy, including the sequential application of hormonal agents and/or cytotoxic chemotherapy agents (Gradishar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is well-known that liver is the third most common site for the metastasis of BCa, resulting in the poorer prognosis than local/ regional, bone, and lung metastases (Kimbung et al, 2016;Ma et al, 2015;C. Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, very few genomic studies have been performed on metastatic samples of breast cancer; they have usually been smaller in size and performed on tumor samples that were not laser-microdissected [2528]. In a larger series of 80 patients [29], the samples were fine-needle aspirates and the histological sub-type was unknown, more than 60% matched-primary tumors being estrogen-receptor positive. In our study, only triple negative and HER2-overexpressing breast cancers were considered.…”
Section: Discussionmentioning
confidence: 99%